A Sex Difference in the Bleeding Time - Bain, Barbara; Forster, T (Thrombosis and Haemostasis, 1980)
The bleeding time by a modified Ivy technique was estimated on 128 normal volunteers, 59 men and 69 women. The bleeding time was found to be significantly longer in women than men (p<.001). This was not attributable to a difference in platelet count nor to any detectable difference in platelet aggregability. It is likely that a difference in blood vessels or supporting tissues is responsible for the observed difference.
Keywords: Bleeding time; Ivy bleeding time; Sex difference